PENYIRAMAN TANAMAN SECARA OTOMATIS MENGGUNAKAN SENSOR SUHU DAN KELEMBABAN BERBASIS MICROCONTROLER - Sitepu, Surianto (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Has designed a tool that serves to maintain the plant to grow well. Plants that grow well in need of treatment were quite good, especially in maintaining soil moisture. So that the land remains under inert conditions in accordance with the standard requirements necessary plants enough water. For that need attention regularly for watering plants. The automatic Plant Watering prototype uses temperature sensors and inertial-based Microcontroller Arduino Uno can be used in the treatment plant without the need to set watering schedules. In order for watering is not carried out during the day or during the scorching sun, the temperature sensor is used. Arduino microcontroller pin which has 14 digital input/output, which serves as the center of the brain process or the automatic sprinklers. The system was designed using a motor driver to drive the motor to pump water watering. Watering can prototype uses temperature sensors and inertial-based microcontroller Arduino Uno to move in automation tools for soil moisture has not been reached. If the soil moisture has been reached then the pump will stop watering the plants.